Statistical physics approach to optimization problems - Ciepliński, Leszek; Jędrzejek, Czesław (Zielona Góra: Uniwersytet Zielonogórski)
Methods of statistical physics are applied to the Travelling Salesman Problem. The starting point is the Hopfield-type Hamiltonian and the most representative benchmark is the 318-city TSP. We find that the recent Ising model neural network implementation by Mehta and Fulop (1993) can be made fully equivalent to the Potts representation proposed by Peterson and Sodeberg (1989).
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka